Calumenin prevents fibroblast senescence and lung aging by promoting vimentin proteostasis - Ting Dong; Xue Jiao; Huirui Wang; Yinghui Gao; Yuliang Xu; Hui Li; Senbiao Fang; Xinyi Chen; Mengmeng Wang; Hanbing Zhu; Nianyu Li; Bo Han; et al. (Proceedings of the National Academy of Sciences, 2026)
Progressive lung fibrosis is linked to aging-related dysfunction in fibroblasts, which remains poorly understood. To investigate the alterations in fibroblasts, particularly the molecular programs driving this profibrotic evolution in the aging lung, we isolated senescent lung fibroblasts from aged mice. We observed aberrant vimentin aggregates, which correlate with accelerated fibroblast senescence. CRISPR-based screening identified calumenin as a chaperone protein essential for vimentin proteostasis. A fibroblast-specific knockout of calumenin promotes the accumulation of vimentin aggregates and profibrotic factors migracytosis, exacerbating fibroblast senescence and lung aging. Mechanistically, calumenin collaborates with the TRiC complex to facilitate proper vimentin folding and recruits the chaperonin subunit Chaperonin Containing TCP1 Subunit 2 (CCT2) to degrade misfolded vimentin aggregates. Pathologically, external profibrotic stimuli trigger calcium transients and induce calumenin degradation, resulting in fibroblast senescence and the initiation of fibrosis. The natural product 9-85, derived from high-content screening, specifically targets and disrupts vimentin aggregates upon stimulation, alleviating aging-related lung fibrosis. Our findings reveal that calumenin coordinates vimentin quality control to shape cell structure and suppress the secretome of senescent fibroblasts, providing a promising therapeutic strategy for aging-related organ fibrosis.